Sociological approach in the research of regional culture as an integrated object of management - Marina Safarbievna Nakhusheva; Svetlana Aslanovna Kirzhinova (Вестник Майкопского государственного технологического университета)
The article studies regional culture as an object of national and regional cultural policy implementation. Scientific literature on various aspects of regional culture has been overviewed, its role in shaping the integrity of the national culture has been given. It is necessary to use a methodology that allows to study regional culture on the basis of interdisciplinary approach. Understanding the processes in the regional culture cannot be done without knowledge of historical information, geoclimatic conditions, specifics of traditions and customs, peculiarities of the psychology of the population of the region, forms of artistic and aesthetic practices, principles of economic determination, forms of political regulation, forms of political regulation. The article focuses on the methods of Cultural Sociology and Management Sociology because the main carriers of the cultural tradition and the object of management are the people. The study reveals the essence of the infrastructure approach to the regional culture management, states the lack of such approach, as it is incapable of taking into account the deep cultural needs of regional society. The need for historically developed traditions in the regional cultural policy, myths and cultural symbols, realized in the daily life of the population and the cultural landscape has been grounded. The goals of cultural policy should not be a quantitative increase in the material resources of cultural institutions, but rather should take into account the needs of a man for freedom, economic stability, civilized development of life location, creativity, balance of work and leisure, participation in making decisions on the development of of cultural space infrastructure.